Conhecimento, atitude e percepções de odontopediatras sobre más oclusões e o tratamento ortodôntico - Pâmella de Moura Dario (2024)
Malocclusion treatment is part of a comprehensive oral health care. During childhood, in addition to genetic factors, children may be affected by dental trauma and other external influences, such as lip/pacifier/thumb sucking, which can lead to the development of significant occlusal changes. These alterations can be identified by a pediatric dentist, who is often the first professional to have contact with the child when oral health care is sought. Considering the possible differences in the understanding of the need for orthodontic intervention on the part of pediatric dentists, the aim of this study was to assess pediatric dentists' knowledge, attitudes, and perceptions about malocclusion and its diagnosis. All pediatric dentists registered within the Regional Dental Council of Minas Gerais (CRO-MG) and the Brazilian Association of Pediatric Dentistry of Minas Gerais (ABOPED-MG) were invited to take part in the study. Pediatric dentists' knowledge, attitudes, and perceptions were measured using a 32- item questionnaire developed by the proponents of this research and sent electronically. The questionnaire had four sections; the first section contained eight questions to assess the demographic characteristics of the sample; the second section had 14 items to assess the knowledge of pediatric dentists about the development of malocclusions and its diagnosis; the third section had five items to assess the attitudes of pediatric dentists about patients’ referral and diagnosis. The fourth section had five items that measured the pediatric dentist's perception of children’s needs and demand for orthodontic treatment. Each item had five response options according to a Likert scale ranging from 1 to 5, for which 1= strongly disagree, 2= disagree, 3= neither agree nor disagree, 4= agree, 5= strongly agree. Descriptive statistics and bivariate analyses were carried out. The sample consisted of 90 pediatric dentists, 80 (88.9%) females and 10 (11.1%) males. With regard to the type of institution from where they obtained the pediatric dentistry degree, 70 (77.8%) studied at private institutions and 20 (22.2%) at public institutions. Of the participants in the sample, 75 (83.3%) reported not having specialized in orthodontics and 15 (16.7%) had already specialized in this area. Males had a significantly higher perception score (more positive perception) than females (p = 0.04). Individuals who had studied pediatric dentistry at a private institution had a more positive perception compared to individuals who had studied at a public institution (p = 0.03). Pediatric dentists who also specialized in orthodontics had a significantly higher knowledge score compared to pediatric dentists who had not specialized in orthodontics (p = 0.02). Individuals who had an undergraduate degree, specialization, a master, and a doctoral degree were the ones who had the higher knowledge score (p = 0.03). One can conclude that male pediatric dentists with a dental degree from private institutions exhibited a more positive perception with respect to malocclusion and its diagnosis. Pediatric dentists who had specialized in orthodontics and those with various levels of training and graduation had a greater knowledge of malocclusion and its diagnosis.